Zircon U-pb ages and magmatic history of the Kashan plutons in the Central Urumieh-Dokhtar magmatic arc, Iran: evidence for neotethyan subduction during paleogene-neogene - Khaksar, Tayebeh; Rashidnejad-Omran, Nematollah; Chen, Fukun; Song, Shu-Guang; Li, Shuang-Qing; Ghaderi, Majid (Journal of earth science, 2020)
The Kashan plutons are situated in the central part of Urumieh-Dokhtar magmatic arc recording subduction-related magmatism within the Alpine-Himalayan orogeny in Iran. These rocks consist of different calc-alkaline plutonic rocks including gabbro, gabbroic diorite, microdiorite, monzodiorite, tonalite, granodiorite, and granite. The plutons were emplaced into the Jurassic sedimentary units (Shemshak Formation) and the Eocene calc-alkaline volcanic and pyroclastic rocks. New U-Pb zircon ages show that the Kashan plutons formed during two main periods at 35.20±0.71 Ma in the Late Eocene (Priabonian) and at 18.90±0.84, 19.26±0.83, 19.30±1.2, and 17.3±1.8 Ma in the Early Miocene (Burdigalian). The reported events in the Kashan plutons imply the final phases of subductionrelated magmatism before the collision which happened between the Arabian and Iranian plates in the Middle Miocene. The plutonic activity in the Kashan region occurred during the transition from Eocene subduction-related setting to Middle Miocene collisional setting.